Perspectives on and from institutional ethnography - Reid, James (Lecturer in childhood studies); Russell, Lisa (Emerald Publishing Limited, 2018)
"This book explores recent developments in Institutional Ethnography (IE) and offers reflective accounts on how IE is being utilised and understood in social research. IE is a sociological sub-discipline developed by Dorothy E. Smith that seeks to explicate the textual mediation of people's everyday experiences in their local sites of being." -- Back cover.
Keywords: Ethnology -- Methodology.; Ethnology -- Research.; Sociology.; elektronické knihy; electronic books